2017
DOI: 10.3390/su9050827
|View full text |Cite
|
Sign up to set email alerts
|

Comparative LCA of Alternative Scenarios for Waste Treatment: The Case of Food Waste Production by the Mass-Retail Sector

Abstract: Food waste is one of the most important issues taken into account by the European Union due to its negative environmental, economic and social impacts. The treatment of food waste through recycling processes represents a solution for food waste minimisation. Concerning, in particular, the retail sector, it is necessary to define strategies for retail-oriented sustainable food waste management. The aim of this study is to compare the potential environmental impacts related to five scenarios (landfill, incinerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 24 publications
2
65
0
Order By: Relevance
“…This effect is not reduced by the composting process which has even a higher impact on Climate Change category. The results of the study are also confirmed by the study of Mondello et al 2017 [28], which report very similar values for acidification, eutrophication and climate change. In the study of Mondello et al [28] four scenarios are compared: landfill, incineration, composting, biogas and insects production with the food waste, to obtain proteins.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This effect is not reduced by the composting process which has even a higher impact on Climate Change category. The results of the study are also confirmed by the study of Mondello et al 2017 [28], which report very similar values for acidification, eutrophication and climate change. In the study of Mondello et al [28] four scenarios are compared: landfill, incineration, composting, biogas and insects production with the food waste, to obtain proteins.…”
Section: Discussionsupporting
confidence: 87%
“…The results of the study are also confirmed by the study of Mondello et al 2017 [28], which report very similar values for acidification, eutrophication and climate change. In the study of Mondello et al [28] four scenarios are compared: landfill, incineration, composting, biogas and insects production with the food waste, to obtain proteins. Of all the compared scenarios biogas confirms to be the more convenient at least in the Climate change category.…”
Section: Discussionsupporting
confidence: 87%
“…The CML-IA baseline method elaborates the problem-oriented approach. The CML method support that elevated level of detail allowing to develop a specific environmental picture of each scenario [31]. The GWP was applied and the characterization model, as developed by the Intergovernmental Panel on Climate Change (IPCC), was selected for the development of characterization factors.…”
Section: Life Cycle Impact Assessmentmentioning
confidence: 99%
“…Quantification of environmental impacts was performed for four impact categories (global warming potential, land use, water footprint and energy demand). Calculations were based on average values from numerous LCA studies performed for food waste treatment with anaerobic digestion [38][39][40][41][42][43][44][45][46][47][48][49][50] , composting [45,49,[51][52][53][54][55][56][57], incineration [38,45,47,48,50], wastewater treatment [58][59][60][61], feeding to pets [62][63][64] and other methods which represent average impact values of all other waste treatment methods. Calculated average LCA impacts were multiplied by the relevant mass flows of avoidable food waste at household level to determine the overall effect of avoidable food waste treatment with current technologies.…”
Section: Methodsmentioning
confidence: 99%